Exploring Linguistic Elements In Students’ Written Discussion Texts - Erna Widyawati; Siti Fhadillah (Journal of Language, Literature, and Educational Research, 2025)
Purpose of the study: This study aims to examine the language features used by students in writing discussion texts, specifically identifying the frequency and type of features such as modal verbs, conjunctions, and conditional clauses. Methodology: This qualitative descriptive study used documentation as the data collection technique. The research analyzed 28 discussion texts written by third-semester students in the Genre-Based Writing course at the English Education Department, UIN Walisongo. Analysis was conducted using Feez’s (1998) framework and the categorization of connectors by Celce-Murcia and Larsen-Freeman (1999). Main Findings: The study revealed that students frequently used modal verbs, particularly “can” and “will,” to express hedging and certainty. Causal connectors like “because” were used more than sequential ones, reflecting the argumentative nature of the texts. However, conditional clauses were underutilized or often misapplied. The texts exhibited general awareness of discussion text features but lacked full mastery in applying them correctly, especially in balancing argumentation and reasoning. Novelty/Originality of this study: This study contributes to genre-based writing pedagogy by specifically mapping the linguistic elements used in students’ discussion texts. Unlike prior research that mainly addressed discourse markers or argument structure, this study focuses on the integration of specific language features, offering insight into students’ actual grammatical competence within the context of academic genres.